Factor Structure of Opportunity to Learn for Students with and without Disabilities - Cawthon, Stephanie Washbourn; Lockhart, Leland; Kaye, Alyssa; Beretvas, Tasha (Education Policy Analysis Archives, 2012)
Opportunity to Learn (OTL) stems from the basic premise that there is an important relationship between the quality and intensity of classroom instruction and students’ levels of academic success. For many students with disabilities, an emphasis on OTL has become national priority, yet measuring its impact is a complex challenge. The first purpose of this study was to explore the factorial validity of OTL using indicators found in the 2005 4th grade National Assessment of Educational Progress (NAEP). The study entailed confirmatory factor analyses for potential OTL factors including teacher preparation, professional development, classroom activities, and access to technology. Separate factor analyses were conducted using the reading and mathematics datasets. The authors then looked at the degree to which OTL factors influenced NAEP estimates of ability for both students with disabilities and their non-disabled peers. The following three OTL factors differentially predicted student scores: classroom activities (reading), student constructed projects (reading), and using calculators for instruction (mathematics). For the remaining three reading factors and seven mathematics factors, there were no differences in the relationship between the factors and scores for students with and without disabilities.